ANALISIS PENDAPATAN USAHA AYAM BROILER DI KECAMATAN JALAKSANA KABUPATEN KUNINGAN JAWA BARAT - H. F. Alfa; T Ekowati; M Handayani (MEDIAGRO, 2016)
Thepresent study was conducted to determine the income of broiler farm in the District Jalaksana. This study used survey method by means of direct observation, and supported by questionnaire directly with farmersin the District Jalaksana, Kuningan Region, West Java which began in February 2015 to March 2015. The research was conducted in several stages, which includes determining the location, to determine the respondents, data collection and analysis of research data and preparing reports. The data obtained and analyzed quantitatively collected. Quantitative analysis is used to determine the amount of capital, cost of production, reception, and revenue. Data were analyzed using multiple linear regression and One sample t-test. Before the data were analyzed by multiple linear regression and One Sample t-test to be tested normality, if the normal data using parametric tests and if not normal using non-parametric test. Normality test is done to determine the condition of the data obtained from the study, so that further analysis can be determined models are most appropriate. The data obtained from the study were then processed and analyzed descriptively to determine the factors that affect revenue, the data obtained are processed by a computer program windows SPSS (Stastistical Product Service Solution). The results of this study indicate that income broiler farm in Districts Jalaksana influenced by independent variables like salary worker, feed prices, the price of DOC, rice husk, OVK and the amount of livestock sold. This is evidenced from the results of the test F, where F count which is greater, which means that overall there is a significant relationship between all independent variables and the dependent variable. The amount of Value Average Revenue broiler chicken farms in the District Jalaksana that has IDR 18.449.890 / year. The average size of the profitability of respondents broiler chicken farm was 3.79%. Keywords: broilers chicken; spending cost; income; profitability